2006
DOI: 10.2322/tjsass.48.229
|View full text |Cite
|
Sign up to set email alerts
|

Butt Welding Joint of Aluminum Alloy by Space GHTA Welding Process in Vacuum

Abstract: Aluminum alloys have been used widely in constructing various space structures including the International Space Station (ISS) and launch vehicles. For space applications, welding experiments on aluminum alloy were performed using the GHTA (Gas Hollow Tungsten Arc) welding process using a filler wire feeder in a vacuum. We investigated the melting phenomenon of the base metal and filler wire, bead formation, and the effects of wire feed speed on melting characteristics. The melting mechanism in the base metal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Influence of wire-feed speed on weld metal dimensions, morphology, and weld bead appearance During the welding of aluminum and its alloys, the aluminum-oxide films that form on the surface of the molten pool must be removed, since otherwise sound weld metal cannot be obtained. 12) Space GHTA welding using pulsed DC current is able to remove the aluminum-oxide films on the molten pool under the arc impact force due to the peak current. However, the plasma stream and arc impact force impel the left portion of the molten pool toward the center of the pipe, causing the weld metal to penetrate the inner wall of the pipe and protrude into it during welding under microgravity.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Influence of wire-feed speed on weld metal dimensions, morphology, and weld bead appearance During the welding of aluminum and its alloys, the aluminum-oxide films that form on the surface of the molten pool must be removed, since otherwise sound weld metal cannot be obtained. 12) Space GHTA welding using pulsed DC current is able to remove the aluminum-oxide films on the molten pool under the arc impact force due to the peak current. However, the plasma stream and arc impact force impel the left portion of the molten pool toward the center of the pipe, causing the weld metal to penetrate the inner wall of the pipe and protrude into it during welding under microgravity.…”
Section: )mentioning
confidence: 99%
“…A technique has also been developed for removing aluminum-oxide film on workpieces using a pulsed electrical current in space GHTA welding. 11,12) A butt welding experiment performed in a simulated space environment demonstrated that space GHTA welding can be used on aluminum pipes. 13) However, the throat thickness was too small in the weld metal due to the arc impact force (i.e., the impact force produced by the arc during a pulse; it is generated by the momentum difference of the plasma stream when the pulse is turned on and off), and this reduced the joint strength.…”
Section: Introductionmentioning
confidence: 99%